Two new species of Americerura St. Laurent & Goldstein, 2023 from Brazil (Lepidoptera: Notodontidae, Cerurinae) - Vitor O. Becker (SHILAP)
Ten species of Americerura St. Laurent & Goldstein, 2023 are represented in Brazil: A. annulifera (Berg, 1878), A. argynnis (Schaus, 1901), A. dandon (Druce, 1894), A. lancea (Schaus, 1905), A. purusa (Schaus, 1928), A. rarata (Walker, 1865), A. rivera (Schaus, 1901) and A. splendens (Jones, 1908), and two described here: A. kalyae Becker, sp. nov. and A. minor Becker sp. nov.